Implementasi Aplikasi Sistem “Pakar Anggrek” Berbasis Android Di Kebun Raya Liwa - Mahfut; Admi Syarif; Tundjung Tripeni Handayani; Sri Wahyuningsih; Kurnia Muludi; Muhammad Irfan Ardiansyah (CV. Multi Kreasi Media, 2023)
Natural orchids are one of the original flora collections in Liwa Botanical Gardens that need to be preserved. Based on the results of our previous research, it is known that some natural orchids show symptoms of disease infection. The Liwa Botanical Gardens do not yet know a safe disease infection control technique. Disease control is still using pesticides that are harmful to the environment. The results of our previous research have resulted in new methods and solutions for disease control through a web-based expert system. This method was considered very helpful for diagnosis but was considered inefficient, so the Android-based